How Much Could Sexuality Cost - Chukhrov, Keti (Stasis, 2016)
Sexuality is not possible without phantasm, phantasm is not possible without the imaginaries maintained by private property. Private property resides in surplus economy. Surplus economy is libidinal. The question would then be: how much could sexuality cost? Or does sexuality vanish if the economy stops to be libidinal?